2022
DOI: 10.1111/trf.16932
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhemolysis in a patient with sickle cell disease and recent SARS‐CoV‐2 infection, with complex auto‐ and alloantibody work‐up, successfully treated with tocilizumab

Abstract: Background: Hyperhemolysis syndrome (HHS) is a severe delayed hemolytic transfusion reaction seen in sickle cell disease (SCD) patients, characterized by destruction of donor and recipient RBCs. It results in a drop in hemoglobin to below pretransfusion levels and frequently reticulocytopenia. Case Report: We report a case of a man in his thirties with SCD with a recent hospitalization 2 weeks prior for COVID-19. His red cell antibody history included anti-Fy(a) and warm autoantibody. At that time, he was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In contrast, Alkindi et al ( 31 ) show that the impact of COVID-19 on the morbidity and mortality of vaso-occlusive crises among individuals with sickle cell anemia was not significant. The occurrence of other sickle cell complications in the context of COVID-19, such as osteonecrosis, acute hemolytic crisis, post-transfusion hyperhemolysis syndrome, and splenic sequestration, has also been reported, although in a minor incidence ( 31 , 65 , 89 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Alkindi et al ( 31 ) show that the impact of COVID-19 on the morbidity and mortality of vaso-occlusive crises among individuals with sickle cell anemia was not significant. The occurrence of other sickle cell complications in the context of COVID-19, such as osteonecrosis, acute hemolytic crisis, post-transfusion hyperhemolysis syndrome, and splenic sequestration, has also been reported, although in a minor incidence ( 31 , 65 , 89 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of tocilizumab, an anti-human IL-6 receptor monoclonal antibody that inhibits signal transduction by binding to sIL-6R and mIL-6R, has been described in some case reports of sickle cell individuals infected by the SARS-CoV-2, demonstrating successful results ( 74 , 77 , 79 , 97 ). This resource, which has even been made available to the general population in some places, should be considered for patients at higher risk of developing a hyperinflammatory syndrome or sickle cell complications, for example ( 74 , 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several potential causative mechanisms were discussed previously, including macrophage hemophagocytosis and "bystander hemolysis." In support of the activated macrophage hypothesis, recent case reports have indicated that treatment with tocilizumab can result in resolution of hemolysis in refractory or difcult cases [9][10][11]. Tocilizumab is a humanized monoclonal antibody directed against the interleukin-6 receptor (IL-6R) [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no prospective studies that confirm the effectiveness and lack of response has also been reported [60]. Furthermore, there are increasing reports of successful treatment with anti-IL-6 receptor monoclonal antibodies such as tocilizumab, particularly in patients with SCD, as they have higher levels of circulating cytokines such as IL-1, TNF-α, and IL-6 [50,61]. Although there are promising case reports, further study is needed to verify the efficacy [51,52].…”
Section: Corticosteroids Eculizumabmentioning
confidence: 99%